Hubungan Tingkat Stres dengan Sindrom Pramenstruasi pada Mahasiswi Fakultas Kedokteran Angkatan 2021 Universitas Tarumanagara - Fadhilah, Windy Hazmi; Herdiman, Julia (Jurnal Kesehatan Andalas, 2022)
Premenstrual syndrome (PMS) is physical and non-physical symptoms experienced by women of the reproductive age two to fourteen days before menstruation. One of the factors can cause PMS is stress. Objective: To determined the correlation between stress and premenstrual syndrome among year 2021 Faculty of Medicine students at University of Tarumanagara. Methods: This research was an observational analytic study with a cross-sectional research design. The stress variable was measured using the Depression Anxiety Stress Scales-21 (DASS-21) questionnaire and the premenstrual syndrome variable was measured based on prospective questionnaire by the American College of Obstetricians and Gynecologists (ACOG). The number of respondents obtained was 138 and the chi-square test was analyzed as a hypothesis test. Results: There were 56 (62,2%) respondents classified as having stress and experienced PMS, while 15 (31,3%) respondents not having stress experienced PMS. The 34 (37,8%) respondents were classified as being stressed but not experiencing PMS, and 33 (68,8%) respondents were not stressed and not experiencing PMS. The affective and somatic symptoms most often experienced irritability (77,54%) and joint or muscle pain (49,28%). There was a significant relationship between stress and premenstrual syndrome with p-value = 0,001 (p-value <0,05). Conclusion: There is a statistically significant relationship between stress and PMS (p<0,05). Affective symptoms were felt more than the somatic ones.Keywords: DASS-21, diagnostic criteria of PMS, premenstrual syndrome, stress